Peran Kepemimpinan Perempuan dalam Memajukan Lembaga Pendidikan Islam (Studi Kepemimpinan Kepala Sekolah) SDIT 1 Daarussalaam Sangatta - Ramadhan, Muhammad Fadhil; Ifendi, Mahfud; Velyna, Tri (JURNAL ILMU PENDIDIKAN & SOSIAL (SINOVA), 2025)
This study examines female leadership in developing Islamic educational institutions at SDIT 1 Daarussalaam, North Sangatta. The background of this research is the persistent social stigma that questions women's capabilities as leaders, particularly within Islamic education settings. This study employs a descriptive qualitative approach through observation and in-depth interviews with the principal, teachers, and staff, supported by secondary data from school documents. The findings reveal that female leadership at this school is based on professional competence and traits such as gentleness, empathy, and a collaborative approach. Supporting factors for success include the use of technology and strong team cooperation. On the other hand, challenges arise from limited communication with male colleagues and difficulties in interacting with male parents. This study contributes theoretically and practically by strengthening recognition of women's roles as leaders in Islamic educational institutions. It recommends the implementation of technology-based leadership training and the enhancement of professional communication while maintaining ethical conduct.